PEMBELAJARAN JARAK JAUH DIMASA PANDEMI COVID-19 MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA SMPN 2 KOTABARU - Muhammad Iqbal Harisuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2020)
This research is about learning mathematics by distance learning is intended as an effort to improve the ability to understand concepts in mathematics learning. The purpose of this study was to determine the increase in the conceptual understanding of students who received mathematics learning by distance learning, as well as to determine students' attitudes towards learning mathematics by distance learning. The research method used was Expo Facto research. The independent variable in this study is distance learning and the dependent variable is the students' ability to understand mathematical concepts. The sample in this study were students of class VII SMP Negeri 2 Kotabaru in the odd semester of the 2020/2021 school year who were randomly selected. The instruments used in this study were test and non-test instruments. The test instrument for students' ability to understand mathematical concepts is in the form of descriptions and non-tests in the form of an attitude scale questionnaire. The data analysis technique used is quantitative data and qualitative data using SPSS 20 for Windows and Microsoft Excel software. By using inferential statistics with a significance level of 5% shows an increase in students' ability to understand mathematical concepts by distance learning. To see students' attitudes towards distance learning, a Likert scale is used. The results of qualitative data concluded that almost all students gave negative responses to learning mathematics by distance learning.